FERTILITAS DAN MIGRASI: KEBIJAKAN KEPENDUDUKAN UNTUK MIGRAN DI KABUPATEN SLEMAN - Muhammad Arif Fahrudin Alfana; Sri Rum Giyarsih (Yogyakarta State University, 2015)
The aim of this study was to clarify the role of migrants in promoting lifelong TFR in Yogyakarta (DIY). The study was conducted in Sleman which has the highest number of migrants in DIY. Methods of data collection done by survey of 300 respondents consist of 150 respondent of childbearing age couples migrants and 150 respondent of childbearing age couples non-migrants. Sampling was done by using a multi-stage sampling method. Result from this study is the childbearing age couples migrants have higher level of fertility than the non-migrant ones. This was due to several factors such as the childbearing age couples migrant families have a higher norm, the age of first marriage of childbearing age couples migrants is lower and childbearing age couples migrant’s participation in family planning programs is low. Some population policies that can be taken to improve the dissemination of family planning in the community, giving more attention to migrants in decreasing fertility level, identifying the migrant families further, increasing the human resources officer cadres or field and improve reproductive health education for the generation plan. Keywords: fertility, migrant, population policy